The Effect of Probiotics on Preterm Birth Rates in Pregnant Women After a Threatened Preterm Birth Episode (The PROPEV Trial) - Ester del Barco; Leidy-Alejandra G. Molano; Mireia Vargas; Marta Miserachs; Linda Puerto; Carmen Garrido-Giménez; Zaida Soler; Begoña Muñoz; Laia Pratcorona; Sonia Rimbaut; Mercè Vidal; Marta Dalmau; et al. (Biomedicines)
Introduction: Preterm birth is the leading cause of perinatal mortality worldwide, with prevalence rates showing little reduction. Although mortality rates have decreased, morbidity rates remain concerningly high. In recent years, there has been a surge in studies examining the etiology, risk factors, and management of preterm birth. The use of vaginal probiotics in pregnant women at risk of preterm birth has garnered attention as a potential approach for improving perinatal outcomes and modulating the vaginal microbiota. However, the efficacy of this intervention remains unclear. Therefore, this study explored the impact of vaginal probiotics on perinatal outcomes and vaginal microbiota composition in pregnant women at risk of preterm birth. Materials and Methods: This was a randomized, prospective, longitudinal, double-blind, placebo-controlled, multicentric trial conducted across seven maternities in Spain from October 2017 to August 2022 in pregnant women at risk of preterm birth. Participants were randomly assigned to receive vaginal probiotics containing four lactobacilli strains or a placebo. The primary outcome was to explore a potential correlation between probiotic use among pregnant women at risk of preterm birth and the actual rate of preterm birth before 37 gestational weeks. Secondary outcomes included an evaluation of preterm birth rates, neonatal morbidity, the vaginal microbiota, and changes in the vaginal microbiota after receiving probiotics. Other secondary outcomes were identifying vaginal microbiota patterns associated with preterm birth and exploring potential therapeutic mechanisms involving probiotics. Trial registration: Clinicaltrials.gov, identifier: NCT03689166. Results: A total of 200 participants were included. Of those, birth data were obtained for 181 women. Demographics were similar between both groups. An analysis of perinatal outcomes found no significant differences in preterm birth rates, prematurity rates, gestational weeks at delivery, neonatal complications, time to birth, or latency time to delivery. Microbiota analysis showed no significant differences in vaginal microbiota changes between groups. No serious or unexpected adverse reactions were reported. Conclusions: There were no statistically significant differences for spontaneous preterm birth between pregnant women receiving probiotics and pregnant women receiving the placebo.